PENGARUH MEDIA PEMBELAJARAN MACROMEDIA FLASH TERHADAP HASIL BELAJAR SISWA (Studi Quasi Eksperimen Pada Mata Pelajaran IPS Kelas VIII di SMP Negeri 3 Kuningan) - Vanny Aditiany; Rani Tania Pratiwi (Universitas Kuningan, 2021)
Vanny Aditiany, (2020). The Influence of Learning Media Macromedia Flash on Student Learning Outcomes (Quasi Experimental Study on Social Sciences Subjects for Class VIII at SMP Negeri 3 Kuningan). Essay. Supervisor 1: Dr. Agie Hanggara, M.Pd Supervisor 2: Rani Tania Pratiwi, M.Pd.The problem in this study is the low student learning outcomes. This is evidenced by the acquisition of many student scores below the Minimum Completeness Criteria. The low learning outcomes can be influenced by several factors (both internal and external), one of which is the application of instructional media carried out by the teacher in the learning process. The purpose of this research is to find the effect of Macromedia Flash learning media on student learning outcomes. As for the design in this study using the non-equivalent control group design. Based on the results of the analysis, the following results were obtained. First, there are differences in student learning outcomes between classes using Macromedia Flash learning media and those using Power Point learning media, where the average learning outcomes of the experimental class (81.3) are superior to the average learning outcomes of the control class (75, 7). Second, there is an increase in student learning outcomes between classes using Macromedia Flash learning media and classes using PowerPoint learning media, where the average increase in learning outcomes in the experimental class (35.7) is superior to the average increase in learning outcomes for the control class (14, 1). The suggestions in this research are that there is a need for an adjustment between the Macromedia Flash learning media with teaching materials, time allocation, and adequate facilities in the application of Macromedia Flash learning media.Keywords : Learning Outcomes, Macromedia Flash.